The Roman Catholic Church of Norway and migration challenges. Issue 1 (2nd January 2019) - Hovdelien, Olav
ABSTRACT: Ever since its re-establishment in Norway in 1843, the Roman Catholic Church has grown steadily. On 1 January 2017, the church had a total membership of approximately 150, 000. The reason for the latest, and certainly largest, wave of Catholic migrants to settle in Norway is labour migration resulting from the eastward expansion of the EU in 2004, when Poland and Lithuania joined. About half the Catholic population of Norway originates from these two countries. This article focuses on the following research question: How does the Roman Catholic Church in Norway, represented by sisters in religious communities, priests and ecclesiastical employees, respond to the large influx of Catholic migrants to Norway? The study is based on a qualitative survey consisting of semi-structured interviews with 10 informants, all religious sisters, priests or ecclesiastical employees. Although some informants admit that the strong growth resulting from migration has posed problems, such as tendencies to form 'parallel congregations' based on ethnic origin, most expressed a positive view of this influx of migrants and of the future of the Catholic Church in Norway.